Global epidemiology of occult HBV infection - Allain, Jean-Pierre (Annals of Blood, 2017)
Defining the epidemiology of occult HBV infection (OBI) is difficult because it relies on disparate sets of data and on the respective performance of both hepatitis B surface antigen (HBsAg) and HBV DNA detection and quantification. Higher sensitivity of HBsAg decreases OBI prevalence while increased HBV DNA detection increases such prevalence as two sliding indexes. In addition there is, at best, poor correlation in the levels of these two parameters. The prevalence of OBI in a general population depends on the prevalence of the infection, being in the 1:100–1,000 in high prevalence areas (East Asia and West Africa) but below 1:5,000 in Western Europe, North America and Australasia. As a percentage of overall infection OBI remains small ranging between 0.1% and 0.6%. Many studies selected individuals with anti-HBc as only serologic marker of HBV infection providing a biased view of the epidemiology since a larger number of cases are seen in anti-HBs positive individuals. The prevalence of OBI is higher in males than in females and also varies according to genotype, being particularly high for genotype D and E. It is typically identified in people ≥50 years, decades post-infection but at a younger age in sub-Saharan Africa. OBI prevalence is elevated in chronic liver disease (CLD), percentages ranging between 40% and 75% in HBsAg negative hepatocellular carcinoma (HCC). Immunodeficiency whether acquired or induced triggers OBI as a minor expression of HBV reactivation in anti-HBc carriers. As methods of HBV DNA detection increase in sensitivity, more OBI will be identified but the clinical significance of these extremely low levels of viral genome remains to be determined. In the meantime, proper epidemiologic, unbiased, studies should be conducted in general populations, particularly where the infection prevalence is high.